2006
DOI: 10.1155/2006/784968
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Pain by Exposure of Acupuncture Points to Polarized Light

Abstract: The results show the efficacy of pain suppression by exposure of antinociceptive APs to P light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
2
16
0
1
Order By: Relevance
“…Analgesia occurred at AP exposition to PL of the diode [14] and halogen nature [1][2][3][4][5][6][7][8][9]. In this case, we confirmed the previously obtained new evidence of PL influence on AP.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Analgesia occurred at AP exposition to PL of the diode [14] and halogen nature [1][2][3][4][5][6][7][8][9]. In this case, we confirmed the previously obtained new evidence of PL influence on AP.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies performed at the Bogomolets Institute of Physiology of NAS of Ukraine, revealed weakening of the somatic pain response under the action of nonpolarized R+IR LED light [13] and polarized halogen light [1][2][3][4][5][6][7][8][9]. The results of the above experiments objectively prove the analgesic effect of polarized R+IR LED light.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In mice, as in many other mammals, a clearly pronounced marker of pain behavior, licking of the injured limb, can be observed under conditions of the formalin test. According to the duration of episodes of licking (PRRs), we can indirectly but rather convincingly estimate the intensity and duration of pain [16,17].…”
Section: Methodsmentioning
confidence: 99%
“…This approach leveled the psycho emotional reactions inherent in man. In experiments on the model of formalin-induced pain in animals, it was proved that when applied to the locus of painful inflammation or to the acupuncture point (AP), PILER-light (PL) caused analgesia [13][14][15][16][17][18][19][20][21]. At equal exposure, the effect significantly depended on the wave range of the light radiation.…”
mentioning
confidence: 99%